Endothelial YAP/TAZ Signaling in Angiogenesis and Tumor Vasculature - Hooglugt, Aukie; van der Stoel, Miesje M.; Boon, Reinier A.; Huveneers, Stephan (Frontiers in Oncology, 2021)
Solid tumors are dependent on vascularization for their growth. The hypoxic, stiff and pro-angiogenic tumor microenvironment induces angiogenesis, giving rise to an immature, proliferative and permeable vasculature. The tumor vessels promote tumor metastasis and complicate delivery of anti-cancer therapies. In many types of tumors, YAP/TAZ activation is correlated with increased levels of angiogenesis. In addition, endothelial YAP/TAZ activation is important for the formation of new blood and lymphatic vessels during development. Oncogenic activation of YAP/TAZ in tumor cell growth and invasion has been studied in great detail, however the role of YAP/TAZ within the tumor endothelium remains insufficiently understood, which complicates therapeutic strategies aimed at targeting YAP/TAZ in cancer. Here, we overview the upstream signals from the tumor microenvironment that control endothelial YAP/TAZ activation and explore the role of their downstream targets in driving tumor angiogenesis. We further discuss the potential for anti-cancer treatments and vascular normalization strategies to improve tumor therapies.